Koreliler'in din değiştirme motifleri - Mehmedoğlu, Ali Ulvi; Kim, Heon Choul (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2001)
The purpose of this research is to outline the nature of Korean converts to Islam and canversion motifsinvolved intheir decisions to become Muslims, based on the analysis of the interviews with a group of Korean converts to Islam. It endeavours to understand the psychological and sociological roots of their canversion experiences. To attain this major objective, this research reviews Lafiand and Skonovd's six canversion motifs. Therefore, it is alsa an empirical evaluation of their canversion motifsin Korean Muslims context.